2009
DOI: 10.1007/s00167-009-0878-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic arthrolysis for the treatment of stiffness after total knee replacement gives moderate improvements in range of motion and functional knee scores

Abstract: Twenty-two total knee replacements (TKR's) were treated for stiffness with arthroscopy and arthrolysis. The median follow-up was 38 months. No patients were lost to follow up. Extensive scarring was found and debrided in all of the knees. The mean Oxford Knee Score improved from 42.6 (+/-7.5) to 36.3 (+/-8.5) (P < 0.05) with TKR and from 36.3 (+/-8.5) to 29.3 (+/-9.0) (P < 0.05) with arthroscopic arthrolysis. The mean arc of motion improved from 8-69 degrees post-TKR to 3-105 degrees on table, but declined sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…The average improvement in ROM in degrees for this treatment in these studies was shown to be 36.2°, however we could not ascertain for certain whether or not these improvements were statistically significant because with the exception of three studies (Arbuthnot and Brink [20], Sprague et al [21] and Johnson et al [22]) the p-values were not provided in any of the studies reviewed. The mean improvement in flexion was given in 8 of the 12 studies [2,20,[22][23][24][25][26][27] and came to 35.2°. The mean improvement in extension was described in seven out of 12 studies [2,20,[22][23][24][25][26] and was 6.4°r espectively.…”
Section: Arthroscopic Releasementioning
confidence: 87%
See 2 more Smart Citations
“…The average improvement in ROM in degrees for this treatment in these studies was shown to be 36.2°, however we could not ascertain for certain whether or not these improvements were statistically significant because with the exception of three studies (Arbuthnot and Brink [20], Sprague et al [21] and Johnson et al [22]) the p-values were not provided in any of the studies reviewed. The mean improvement in flexion was given in 8 of the 12 studies [2,20,[22][23][24][25][26][27] and came to 35.2°. The mean improvement in extension was described in seven out of 12 studies [2,20,[22][23][24][25][26] and was 6.4°r espectively.…”
Section: Arthroscopic Releasementioning
confidence: 87%
“…8), complications that occurred were a superficial skin infection in one patient and tenderness in the infrapatellar fat pad in one other patient [19]. One patient had instrument breakage occur during the arthroscopy [20] but this was resolved immediately without any further complications. A superficial wound infection was also reported in one patient in another study [25].…”
Section: Arthroscopic Releasementioning
confidence: 95%
See 1 more Smart Citation
“…According to data from Table 1, in the present study were included 6 patients of 66.5±7.66 (53-74) years old, M/F = 1/5. The average time between TKA and arthroscopic arthrolysis was 7.33 ± 1.86 months (5)(6)(7)(8)(9). The average body mass index (BMI) of the patients was 30.89 ± 4.04 kg/m 2 (26.33-36.20), two patients had a BMI under 30 kg/m 2 and four patients had BMI over 30 kg/m 2 .…”
Section: Experimental Partmentioning
confidence: 99%
“…[3] Arthrofibrosis, defined as abnormal scarring of the joint in which the formation of dense fibrous tissue and tissue metaplasia prevents normal ROM [4], and drastically reduces quality of life of those affected individuals. Prevention of knee stiffness should be started from the TKA surgery by limiting the amount of bone resected, correct positioning of prosthetic components with appropriate ligament balancing, restoring the mechanical and anatomical axes of the lower limb, and proper prosthesis design [5]. Psychological factors such as excessive postoperative pain, which prevent appropriate rehabilitation treatment, as well as poor patient motivation, should not be omitted.…”
mentioning
confidence: 99%